SEISMICITY OF THE BERING STRAIT REGION: EVIDENCE FOR A BERING BLOCK - Mackey K.G.; Fujita K.; Gunbina L.V.; Kovalev V.N.; Imaev V.S.; Kozmin B.M.; Imaeva L.P. (My University, 1997)
Newly compiled Russian and U.S. seismological data support an independent Bering block in motion relative to the North American plate. This motion is likely to be driven by the westward extrusion of southwestern Alaska, resulting from compression in southern Alaska due to subduction of the Pacific plate and terrane accretion. Seismicity extends from central Alaska, through the Bering Strait, and into Chukotka. In eastern Chukotka several southwest trends are evident, some of which continue through the Koryak Highlands to Kamchatka. The seismicity outlines the Bering block, which includes most of the Bering Sea, Chukchi Peninsula, Seward Peninsula, and parts of western Alaska. Focal mechanisms, young basaltic volcanism, and normal faults in western Alaska and Chukotka indicate that the Bering Strait is under northeast-southwest extension. This, in conjunction with thrust faulting in the Koryak Highlands, indicates that the Bering block is rotating clockwise relative to the North American plate.